2011
DOI: 10.4085/1062-6050-46.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Concussion Symptoms of High School Athletes

Abstract: Context: More than 1.6 million sport-related concussions occur every year in the United States, affecting greater than 5% of all high school athletes who participate in contact sports. As more females participate in sports, understanding possible differences in concussion symptoms between sexes becomes more important.Objective: To compare symptoms, symptom resolution time, and time to return to sport between males and females with sport-related concussions.Design: Descriptive epidemiology study. Setting: Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
138
5
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 244 publications
(163 citation statements)
references
References 41 publications
(55 reference statements)
12
138
5
3
Order By: Relevance
“…Another study found that juvenile males and females did not differ on a range of sensorimotor outcomes, which is consistent with our findings of motor‐related deficits in both male and female rats given RmTBI 67. Clinical studies of sex differences following mTBI in high school and collegiate students are currently conflicted; some have reported females are more likely to be cognitively impaired and experience more subjective and objective symptoms,11 while others have reported no differences in the number of symptoms, but sex differences in the type of symptoms experienced 64. Given the significant degree of brain maturation occurring during this critical period of development, sex‐dependent variations, and the differences in symptomology associated with single versus repetitive mTBI, it is not surprising that clinical studies have failed to produce reliable results regarding symptom presentation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Another study found that juvenile males and females did not differ on a range of sensorimotor outcomes, which is consistent with our findings of motor‐related deficits in both male and female rats given RmTBI 67. Clinical studies of sex differences following mTBI in high school and collegiate students are currently conflicted; some have reported females are more likely to be cognitively impaired and experience more subjective and objective symptoms,11 while others have reported no differences in the number of symptoms, but sex differences in the type of symptoms experienced 64. Given the significant degree of brain maturation occurring during this critical period of development, sex‐dependent variations, and the differences in symptomology associated with single versus repetitive mTBI, it is not surprising that clinical studies have failed to produce reliable results regarding symptom presentation.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with epidemiological findings, postinjury symptomology differed between males and females 12, 64. Males given mTBIs exhibited greater impairment on the cognitive task (i.e., NCM), whereas females given mTBIs exhibited increased impairments on the forced swim task.…”
Section: Discussionsupporting
confidence: 75%
“…After sensitivity analysis, the best cut-point score was used for multiple logistic regression, adjusting for gender and age, as symptom report may vary by both age and gender. [32][33][34] The same methods were used substituting our clinical definition of DSR with the PCS criteria. Results of x 2 analysis were considered significant if P , .05.…”
Section: Discussionmentioning
confidence: 99%
“…In that intervening period, athletes may experience a combination of cognitive, somatic and emotional symptoms [9,10] that can impair their ability to complete school or work obligations [11]. Athletes who sustain more concussions are more likely to experience prolonged symptoms [12][13][14].…”
Section: Introductionmentioning
confidence: 99%